COMPARATIVE STUDY ON TOTAL SOLUBLE PROTEINS OF VARIOUS Mucuna SPECIES AND DISSECTING THEIR ROLE IN TRYPSIN INHIBITION (Applied Biological Research, 2023)
Plant seed proteins have pivotal health benefits. However, diminutive  information is available on the presence of total soluble protein (TSP) levels  in major crops. The present study was aimed to extract total soluble  proteins from seven species/varieties of Mucuna and evaluate their activity  for endogenous regulation of proteases. The total soluble proteins and  protease inhibitory activity of various varieties/species of Mucuna were  studied by both qualitative and quantitative methods. The total soluble  proteins isolated were variable (18 to 29%) with maximum proteins in  Mucuna utilis (29%) and minimum in M. pruriens V1 (18.7%). The total  protease inhibitory activities were in the range of 9-18.25 TIU mg-1 with  maximum in M. pruriens (18.25 TIU mg-1) and minimum in M. pruriens V1  (9.78 TIU mg-1). The TSP content and protease inhibitory activities in other  species/varieties were: M. pruriens 27.4% and 18.25 TIU mg-1, M. utilis 29% and 16.67 TIU mg-1, M. monosperma 26.9% and 15.27 TIU mg-1, M.  pruriens V2 21.7% and 13 TIU mg-1, M. hirsute 23.8% and 15.93 TIU mg-1 and M. gigantea 24.3% and 11.98 TIU mg-1, respectively. Electrophoretic  analysis revealed the presence of various trypsin isoinhibitors and multiple  protein bands. The present analysis revealed that Mucuna seeds can be  used as an alternative to protein source and their biological activity  indicated their usefulness in medical field.
Keywords: Mucuna species; native PAGE; protease inhibitor; reverse zymography PAGE; seed storage proteins